Ultra-broadband cyan-to-orange emitting Ba1+xSr1−xGa4O8:Bi3+ phosphors: luminescence control and optical temperature sensing. Issue 5 (2nd January 2020) - Dang, Peipei; Liu, Dongjie; Yun, Xiaohan; Li, Guogang; Huang, Dayu; Lian, Hongzhou; Shang, Mengmeng; Lin, Jun
Abstract : Controllable cyan-to-orange tuning and optical thermometry in Ba1+ x Sr1− x Ga4 O8 :Bi 3+ phosphors with ultra-broadband emission were realized based on crystal filed control at multiple emission centers. Abstract : Herein, we report a new series of Ba1+ x Sr1− x Ga4 O8 :Bi 3+ ( x = 0–0.7) phosphors that exhibit extremely broadband emission, covering almost the entire visible region and extending to the deep-red region, when excited by ultraviolet light. BaSrGa4 O8 :Bi 3+ exhibits two emission bands located at 470 and 570 nm originating from different emission centers. With the gradual substitution of Ba for Sr, both of the emission bands show a red-shift, from 470 to 510 nm and from 570 to 630 nm, respectively. The corresponding full width at half maximum (FWHM) increases from 192 to 283 nm, which is attributed to a superposition of multiple emission centers via crystal field regulation. As a result, the emission can be tuned from cyan to orange across the warm white light region in Ba1+ x Sr1− x Ga4 O8 :Bi 3+ ( x = 0–0.7) systems. Simultaneously, this series of phosphors presents good thermal stability (97% intensity at 150 °C for the Ba1.5 Sr0.5 Ga4 O8 :Bi 3+ sample) and the thermal quenching will decrease with the formation of a solid solution due to the increasing rigidity of the lattice structure. Interestingly, the two emission bands in the representative Ba1+ x Sr1− x Ga4 O8 :Bi 3+ ( x = 0–0.7) sample exhibit different thermal responses to increasing temperature, thus an optical thermometer with color discrimination and good sensitivity is designed. The maximum relative sensitivity ( S r ) is 1.295% K −1 in the temperature range of 7–400 K. The corresponding emission color can be tuned from blue-cyan to orange, including white light. This work presents a rational design strategy for controllable ultra-broadband emission tuning across the white light region and to further explore potential optical sensor applications.